Telemedicine Consultations in Community Hospitals Improve Neonatal Encephalopathy Assessment - Cutler, Anya; Seften, Leah Marie; Craig, Alexa (American Journal of Perinatology, 2025)
We aimed to determine if the implementation of teleconsults in the community hospital would decrease the time to initiation of therapeutic hypothermia (TH).We compared neonates treated with TH prior to implementation of the teleconsult program (pretele) to those treated after (posttele) for the outcomes of time to initiation of TH, seizures, and death/severe injury on brain MRI. We controlled for confounders using multivariable linear and logistic regression models.There were 52 pretele neonates and 49 posttele who were all born in community hospitals and treated with TH. Mothers in the posttele group were older and had higher rates of gestational diabetes. Fewer neonates with mild encephalopathy were cooled in the posttele period (13 [25.0%] pretele vs. 2 [4.1%] posttele). After controlling for gestational diabetes, maternal age, and severity of encephalopathy, there was no difference in time to TH initiation (p = 0.445), brain injury or death (p = 0.136), or seizure (p = 0.433) between the pre-and posttele groups. In the sub-analysis of the posttele group, the time to initiation was 4.50 hours (3.75, 5.00) for those with teleconsults versus 3.25 (2.12, 4.00) hours (p = 0.007) for those without.When comparing pre- to posttele groups, teleconsults in the community hospital did not significantly change the time to initiate TH or result in more adverse short-term outcomes of seizures or death/brain injury. In the sub-analysis of the posttele group, teleconsults did result in delayed initiation of TH but also possibly improved patient selection with fewer mildly encephalopathic neonates treated.
Keywords: therapeutic hypothermia; neonatal encephalopathy; telemedicine